Examining farmers' willingness to grow and allocate land for oilseed crops for biofuel production - Embaye, Weldensie T.; Bergtold, Jason S.; Archer, David; Flora, Cornelia; Andrango, Graciela C.; Odening, Marting; Buysse, Jeroen (My University, 2018)
The purpose of this paper is to determine farmers' willingness to adopt and allocate land for growing non-food oilseeds as bio-energy crops across the western US. A mail survey was conducted in three regions of the western US from randomly selected wheat farmers. Data was analyzed using Heckman's two stage selection model to correct for selection bias. Under favorable contracts, the study found that 58% of sample farmers were willing to adopt oilseeds as bio-energy crops and initially contribute an average of 160 acres of land for production per farm. Concerning farmers' adoption decisions, factors such as experience growing oilseed crops, availability of a nearby crushing facility, use of no till, being a first adopter and having a college degree positively affected adoption, while risk behavior, farm experience and gender negatively affected adoption. With regard to the land allocation decision, factors such as farm income and gender positively affected land allocation decisions, whereas percentage of land rented on a crop share basis, profit ratio (wheat/canola) and livestock ownership negatively affected land allocation decisions.
Keywords: Bio-jet fuel; Contract; Land use; Oilseed; Wheat